2005
DOI: 10.7205/milmed.170.12.1037
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Trauma as Predictors of Military Attrition: A Study of Marine Corps Recruits

Abstract: Recent studies have shown high rates of premilitary trauma exposure among U.S. military enlistees. Given the association of trauma with later stressor vulnerability, it is important to examine the role of premilitary stress and trauma in adaptation to the stress of recruit training. U.S. Marine Corps recruits (N = 1,530) were surveyed for premilitary histories of interpersonal trauma to examine the relationship between premilitary trauma and attrition from recruit training. The majority of the recruits (47.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…Participants were 658 women who completed questionnaires after graduating from a 13-week boot camp training program at Parris Island, South Carolina, as part of a longitudinal study of Marine recruits (see Wolfe et al 2005, for details). Men attend boot camp on the same base, but recruits are segregated by gender during the training period.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were 658 women who completed questionnaires after graduating from a 13-week boot camp training program at Parris Island, South Carolina, as part of a longitudinal study of Marine recruits (see Wolfe et al 2005, for details). Men attend boot camp on the same base, but recruits are segregated by gender during the training period.…”
Section: Participantsmentioning
confidence: 99%
“…Research on the effects of the psychological stress associated with recruit training (boot camp) in the U.S. has identified a number of individual attributes that influence female recruits' adjustment to the military, including cognitive appraisal of stress, social support, and hardiness (Vogt et al 2008), as well as prior experiences of interpersonal trauma (Wolfe et al 2005). Inasmuch as individual attitudes and beliefs play a role in adjustment to the military, one factor that may be particularly relevant for women is gender-role egalitarianism, or beliefs about acceptable roles for women and men in society.…”
Section: Introductionmentioning
confidence: 99%
“…The differences were less pronounced for men, but still significant across childhood physical, verbal, and sexual abuse (Katon et al, 2015). Results also suggest that military enlistees not only report higher levels of childhood abuse, but also report more exposure to various interpersonal traumas both in adolescence and early adulthood as well (Wolfe et al, 2005). A critical review of trauma among female Veterans found that not only do female Veterans report higher rates of trauma exposure than their civilian counterparts, but that they are subsequently at risk for cumulative trauma exposure (Zinzow, Grubaugh, Monnier, Suffoletta-Maierle, & Frueh, 2007).…”
Section: Introductionmentioning
confidence: 56%
“…This type of violence may be seen as a betrayal, and subsequently be more likely to challenge one's core beliefs about the world (Cann et al, 2010;Morgan, Desmarais, Mitchell, & Simons-Rudolph, 2017) or shatter fundamental assumptions (Cann, Calhoun, Addington, & Groleau, 2013;Janoff-Bulman, 1992). Sexual assault in the military has consequences beyond the negative effects on the mental health of the victim, including damage to morale, trust, and unit cohesion; mission degradation; and decreased readiness and retention Stimson, 2013 (Merrill, Stander, Thomsen, Crouch, & Milner, 2006;Stander, Merrill, Thomsen, Crouch, & Milner, 2007), and this association may be particularly strong for female recruits (Wolfe et al, 2005). Understanding that people enter service with previous trauma is necessary to develop programs aimed at coping skills early on in one's military career, before the recruit is likely exposed to additional adverse events common to military life.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Individuals in the US Marine Corps who experienced interpersonal trauma were 1.5 times more likely to drop out of recruit training compared to those without a trauma history. 20 There is a reported increased risk of attrition among some service members, such as the Marines, who have psychiatric diagnoses. 21 We suggest that what is needed is an epidemiologic approach to the mental health effects of service directly in combat or in areas of combat.…”
mentioning
confidence: 99%